THE SIGNIFICANCE OF STRATEGIC MANAGEMENT FOR BUSINESS ORGANIZATIONS - Reyimberdiyev Baburbek Adilbek o’g’li (Galaxy International Interdisciplinary Research Journal, 2023)
This paper highlights the significance of strategic management in business organizations. It provides a comprehensive definition of strategy and explores key elements of strategic management, including strategic vision, objectives, strategy formulation, implementation, evaluation, and corrective action. The research also emphasizes the role of corporate governance in strategic management, particularly the involvement of the board of directors in developing and executing strategies. Additionally, the paper examines different levels of strategy, such as corporate, business, functional, and operational, and emphasizes their importance in effectively managing business organizations. Given the dynamic and competitive nature of the operating environment, the paper underscores the need for businesses to recognize the importance of developing and executing strategies that can establish sustainable competitive advantage.